Desain Rontek Banner Ramadhan untuk Masjid Baiturrahim Jakarta Timur - Ahmad Alberd; Fahuzi Nazari; Yulianto Hadiprawiro; Ahmad Faiz Muntazori; Salwa Nadilah (Abdi Seni, 2025)
The author conducts discussions with the Management of the Baiturrahim Mosque Prosperity Council (DKM) regarding what media needs are needed. DKM Baiturrahim needs to make visual media to welcome the holy month of Ramadan. DKM needs attractive persuasive media, to attract residents to come to the mosque. Based on the needs of DKM Baiturrahim, the author created a Rontek Banner design that contains an invitation to come to the mosque and optimize worship in the holy month of Ramadan. At the stage of the work-making process, the author uses the Design Design Thinking method for the work-making process. Design Thinking is a human-centered approach to innovation that consists of five iterative stages: empathize, define, ideate, process and test. Each stage plays an important role in developing solutions that effectively address user needs. As a result, the team created a rontek design with the topic of congregational prayer and the virtues of fasting in the month of Ramadan. The author produced 10 designs that were submitted and installed in the inner and outer areas of the mosque. Keywords: rontek banner dakwah; visual dakwah; visual media ramadhan